The Conundrum Of National Identity: Naturalisation Of India As A National Collectivity - A Postcolonial Perspective - T.S, Yashavantha; H.K., Shivalingaswamy (International Journal of Psychosocial Rehabilitation, 2020)
This paper critically examines the concept of 'imagined homogeneity' and its implications for understanding India as a national collectivity in a postcolonial context. It scrutinizes the impact of British colonial rule on the formation of India's national identity, detailing how colonial strategies reinforced an oversimplified perception of India, a diverse and multifaceted country. It explores how this 'imagined homogeneity' has been questioned in the postcolonial era, leading to the emergence of regional and identity-based politics and resulting in numerous conflicts. The challenges and complexities of achieving national cohesion in post-colonial India, particularly given its cultural, linguistic, and religious diversity, are also addressed. The study's findings emphasize the need for a more nuanced understanding of India's diverse identities and the implications for the nation's attempts at naturalization in the postcolonial era.